Community services and shared responsibility in the conciliation of family timetables: the situation of urban Galician children - M Belen Caballo Villar; Rita Gradaille Pernas; Tania Merelas Iglesias (Sociedad Iberoamericana de Pedagogía Social, 2012)
SEPA is a research team from the Universidad de Santiago de Compostela, Spain supervised by Professor Jose Antonio Caride and has spent the last 10 years working on questions related to the time allocated to education and social issues 1. The team focuses its studies on the timetables of the school day and its influence in socialization and infant´s quality of life, leisure time, etc. Related to this research line, in 2008 the team started a biannual project for studying difficulties in the conciliation in daily life for families with children who go to primary school, contextualizing it in urban Galicia, Spain. Three subjects have a big presence in the analysis: school times, family life and children's leisure. In this work we are presenting some of the conclusions of this study, emphasizing the importance of social educative services and family co-responsibility to guarantee the quality of life in childhood.